2020
DOI: 10.3389/fped.2020.00219
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Patterns of Congenital Heart Disease Among Jordanian Infants, a Cohort Study From a University Tertiary Center

Abstract: Background: Data is limited about the incidence of congenital heart disease in Jordan. The goal of this study is to determine the incidence and patterns of congenital heart diseases (CHD) among Jordanian infants evaluated at King Abdullah University Hospital. Methods: A retrospective chart review was conducted for all infants who had an echocardiogram evaluation in the 3-years period July 2016-June 2019. All included infants had a 2-dimentional echocardiogram with a Doppler vascular study performed by the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…In our study Tetralogy of Fallot was the most common cyanotic structural heart defect with frequency of 25.3%. This observation is consistent with different studies conducted in Jordan 11,12 , India 13,14,4 , Pakistan 15,16 , and globally. 17 TGA was the most common CCHD in neonatal period (27.9%) in a study conducted in Srinagar.…”
Section: Resultssupporting
confidence: 93%
“…In our study Tetralogy of Fallot was the most common cyanotic structural heart defect with frequency of 25.3%. This observation is consistent with different studies conducted in Jordan 11,12 , India 13,14,4 , Pakistan 15,16 , and globally. 17 TGA was the most common CCHD in neonatal period (27.9%) in a study conducted in Srinagar.…”
Section: Resultssupporting
confidence: 93%
“…4 The second most common type of cyanotic CHD is TGA, with a prevalence of about 7% of all CHD events TGA cases. 5 Studies by Zhao et al 12 in China, Meshram and Gajimwar 14 in India, and Khasawneh et al 18 in Jordan found that TOF and TGA had the highest prevalence, respectively. This study had the same results as the theory and several previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Khasawneh et al also mentioned that murmurs and cyanosis are the most common clinical signs and symptoms and are the main referral indications in cyanotic CHD patients. 18,19 Cyanosis is a bluish discoloration of the skin and mucous membranes due to an increase in the concentration of reduced hemoglobin in the bloodstream. 20 In patients with cyanotic CHD, a shunt occurs from right to left and there is a mixing of oxygen-rich blood with carbon-dioxide-rich blood so that the blood flowing throughout the body has decreased oxygen saturation, resulting in manifestations of cyanosis in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also consistent with other studies done in India and outside. 15,16 In both cyanotic and acyanotic CHDs, the post tricuspid anomalies were most prevalent. VSD, PDA, APW were the most common anomalies in acyanotic group, whereas the TOF, TOF-PA, TETCANAL group of anomalies were the most common cyanotic anomalies.…”
Section: Discussionmentioning
confidence: 99%